Fungsi Tortor Mangaloalo Tondong Pada Acara Par Roh Parmaen dalam Upacara Pernikahan Simalungun di Desa Sipispis Kabupaten Serdang Bedagai - Noni Pitaloka Damanik (Gesture: Jurnal Seni Tari, 2016)
The function of TortorMangaloaloTondong on Occasion of Par RohParmaen in WeddingCeremony Simalungun at SipispisSerdangBedagai district.SendratasikDepartement. DanceEducation Program Fakulty of language and Art. State University of Medan. This studydiscusses about the function of TortorMangaloaloTondong on Occasion of Par Rohmaen inWedding Ceremony Simalungun at SipispisSerdangBedagai district. The theory is used theoryof function. Population of study aretradisional leaders. Simalungun people who knows aboutTortorMangaloaloTondong. The data collection was conducted by real work methods it wereinterviews, direct observation, documentation and literature study. The methods is used in thisstudy is qualitative method and descriptive approach. The result of the revealed thatTortorMangaloaloTondongfunction were server as the communication between human andhuman (suhutbolon and tondong). Tondong respected for delivering advice to suhutbolon andbride in tortor, humans communication to God were gratitude to God because the weddingceremony had done clearly, human and nature to see the weather, determine a good day for thewedding ceremony.